Fragility in elderly residents of long-term care institution - Graciela Maria Carneiro Maciel; Hilderjane Carla da Silva; Maria Célia de Freitas; Rejane Maria Paiva de Menezes (Universidade Federal de Santa Maria, 2014)
Doi: 10.5902/2179769211328 Objective: to identify the level of fragility of institutionalized elderly women and, thereafter, indicate diagnoses, interventions and nursing outcomes. Method: cross-sectional study, conducted in April and May 2012, in a long-term institution for elderly women in Fortaleza. The Edmonton Frail Scale was applied, considering nine domains. The International Taxonomy of North American Nursing Diagnosis Association, Nursing Intervention Classification and Nursing Outcomes Classification were utilized to list the diagnoses, interventions and nursing outcomes.  Results: 16 out of 24 elderlies (66.6%) were fragile. According to the level of frailty, 7 (29.1%) were mildly frail, 2 (8.3%) were moderately frail, 7 (29.1%) were severely frail. The adopted domains of the scale were: functional independence, medicine usage, continence and functional performance, which led to the identification of six nursing diagnoses; interventions and results. Conclusions: the use of the scale allowed identification of levels of fragility, as well as the suggestion of diagnoses, interventions and expected outcomes.